Technologic processes of improvement of secondary aluminum alloys quality - O. N. Kalenik; S. E. Shurankov; V. L. Trihushevsky; S. L. Rimoshevsky (Литьë и металлургия, 2000)
The article is dedicated to the solution of a very important problem— improvement of quality of secondary alloys, received out of oxidized material wastes.